Samuel Beckett : the art of rhetoric - Morot-Sir, Edouard; Harper, Howard; McMillan, Dougald (Chapel Hill : University of North Carolina Press, 2018)
Collected essays from a symposium held in April 1974, at the University of North Carolina at Chapel Hill, this volume analyzes Beckett's philosophy, rhetoric, poetry, and novels.
1. Murphy, or the Beginning of an Esthetic of Monstrosity2. Statistics on Proper Names in Murphy; 3. The Addenda to Samuel Beckett's Watt; 4. A Mythic Reading of Molloy; 5. The Couples in Comment c'est; 6. How it is; V. WORKING WITH BECKETT; Back Cover.
Online resource; title from PDF title page (EBSCO, viewed August 29, 2018).
Originally published in 1976.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Beckett, Samuel, -- 1906-1989 -- Criticism and interpretation; Beckett, Samuel, -- 1906-1989 -- Critique et interprétation -- Congrès.; Beckett, Samuel, -- 1906-1989; Beckett, Samuel; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Rhetorik; Französisch.; Englisch; proceedings (reports); Conference papers and proceedings; Criticism, interpretation, etc; Conference papers and proceedings; Actes de congrès.